Reformulation of the Prosecutor’s Office’s Regulatory Role in the Legislative Process for Sustainable Economic Development - I Gede Willy Pramana; Gde Made Swardhana; Desak Putu Dewi Kasih; Sagung Putri M.E. Purwani (Asian Journal of Social and Humanities, 2026)
The phenomenon of sustainable economic development in Indonesia reveals the increasing complexity of national strategic policies and projects, which necessitate preventive and sustainable legal safeguarding. Normatively, the Indonesian Prosecutor's Office is positioned not only as a repressive law enforcement body but also as an institution with preventive and protective functions through its law enforcement intelligence authority, as stipulated in Article 30B of Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia (the Amendment to the Prosecutor's Law). However, its implementation reveals that the Prosecutor's Office's role in the legislative process and development policy planning has not been optimally actualized. Juridically, this is due to the ambiguous norm (vague norm) in Article 34 of the Amended Prosecutor's Law, which uses the permissive phrase "may" in providing legal considerations to the President and other government agencies. This phrasing fails to establish a legal obligation for the Prosecutor's Office's involvement in the development legislation process. Sociologically, the absence of a clear regulatory model and mechanism regarding the Prosecutor's Office's security function during the early stages of policy formulation leads to weak preventive legal supervision. Consequently, this creates fertile ground for conflicts of interest, legal uncertainty, and potential abuse of authority in sustainable economic development. This research employs a normative legal research method, focusing on the ambiguity of norms, particularly the phrase "may" in Article 34 of the Amended Prosecutor's Law. This ambiguity underscores the urgent need for a regulatory framework that explicitly mandates the active role of the Prosecutor's Office in the legislative process at every level, given its unique authority in law enforcement intelligence and its mandate to provide legal considerations to the President and other government agencies.